Two new species of Erysiphe sect. Uncinula (erysiphales): Erysiphe fernandoae and E. michikoae - Jamjan Meeboon (2018)
Two new species of Erysiphe section Uncinula are described and illustrated based on the molecular and morphological analyses: (1) Erysiphe fernandoae sp. nov. on Fernandoa adenophylla is distinct from other Erysiphe species on the plant family Bignoniaceae by having smaller asci, ca 12 appendages per chasmothecium and being found only in Asia; (2) Erysiphe michikoae sp. nov. on Celtis jessoensis differs from Erysiphe kusanoi on other Celtis species in having smaller chasmothecial, ascal and ascospore dimensions, and fewer number of chasmothecium appendages. The phylogenetic relationships of the two new species with other closely related species are discussed based on 28S and ITS rDNA sequences. © 2012 The Mycological Society of Japan. Published by Elsevier B.V. All rights reserved.